The Toilet Paper Entrepreneur The tell-it-like-it-is guide to cleaning up in business, even if you are at the end of your roll - Mike Michalowicz (New Jersey Obsidian Launch, 2008)
"Never started a company before? Struggling with little or no cash? Have no experience, no baseline to judge your progress against? Thank God! You've got a shot at making this work." So says Mike Michalowicz, author of The Toilet Paper Entrepreneur, a business book that is so uniquely useful, so raw and entertaining, it reads like the brainchild of Steve Jobs and Chris Rock. The founder of three multimillion-dollar companies, including Obsidian Launch, a company that partners with first-time entrepreneurs to grow their concepts into industry leaders, Mike Michalowicz knows what it really takes to spin your great idea into pure gold. Whether you're just starting out or have been at this for years, Mike's "get real" approach to business is a much-needed swift kick in the pants. In this book, you'll discover: * Why a business plan is a total waste of your time. * Why fulfilling your own needs is the first and last order of business. * Which three sheets of paper you need to successfully launch, manage and grow your business. * How to get started in business with little or no money. * How to find and exploit resources that no one else knows about. * How to stop procrastinating and take action NOW!
Keywords: Entrepreneurship; Nonfiction; Business